2017
DOI: 10.1021/acs.macromol.7b00121
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Thermal Stability and Living Fashion in α-Diimine–Nickel-Catalyzed (Co)polymerization of Ethylene and Polar Monomer by Increasing the Steric Bulk of Ligand Backbone

Abstract: Development of thermally stable nickel-based catalysts is highly desirable for industrial gas-phase olefin polymerizations. On the basis of the strategy of promoting the thermostability of nickel catalyst by the ligand backbone, we herein reported novel dibenzobarrelene-derived α-diimine nickel precatalysts for ethylene polymerization. Increasing the steric bulk on the ligand backbone was expected to inhibit the N-aryl rotation of the α-diimine ligands by the repulsive interactions, thus enhancing thermal stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
142
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(145 citation statements)
references
References 61 publications
(98 reference statements)
2
142
0
1
Order By: Relevance
“…Wu and co‐workers extended these efforts to restrict N ‐aryl rotations via α ‐diimine modifications to include catalysts 21 and 22 , which feature a ‘wedge‐shaped’ dibenzobarrelene‐derived α ‐diimine ligand (Fig. ) . As a note, a related Ni α ‐diimine catalyst containing an unsubstituted dibenzobarrelene backbone was previously reported by Coates and co‐workers, and was shown to polymerize ethylene in a living manner at room temperature .…”
Section: Thermally Stable Ni‐ and Pd‐based Catalystsmentioning
confidence: 93%
See 1 more Smart Citation
“…Wu and co‐workers extended these efforts to restrict N ‐aryl rotations via α ‐diimine modifications to include catalysts 21 and 22 , which feature a ‘wedge‐shaped’ dibenzobarrelene‐derived α ‐diimine ligand (Fig. ) . As a note, a related Ni α ‐diimine catalyst containing an unsubstituted dibenzobarrelene backbone was previously reported by Coates and co‐workers, and was shown to polymerize ethylene in a living manner at room temperature .…”
Section: Thermally Stable Ni‐ and Pd‐based Catalystsmentioning
confidence: 93%
“…More specifically, they demonstrated that the 2,6‐dimethylphenyl‐substituted catalyst 21 can polymerize ethylene in a living fashion at temperatures as high as 65 °C, whereas polymerization using the bulkier 2,6‐diisopropylphenyl‐substituted catalyst 22 proved to be living at temperatures as high as 80 °C. Further increasing polymerization temperatures to 100 °C revealed that while catalyst 22 remains active, it did deactivate slowly over the course of the 60 min polymerization …”
Section: Thermally Stable Ni‐ and Pd‐based Catalystsmentioning
confidence: 99%
“…[41] Considering the impressive reactivity of the Brookhart catalysts toward norbornene, [42] and their excellent tolerance toward ester functionalities,C hen and co-workers successfully copolymerized ethylene with polar functionalized norbornenes using a-diimine palladium catalysts. [43,44] Coates and co-workers [45] and Gao and co-workers [46] demonstrated that a-diimine nickel catalysts can mediate ethylene copolymerization with methyl 10-undecenoate.…”
Section: Developments Using the Brookhart And Drent Catalystsmentioning
confidence: 99%
“…However, such bulky substituents were found to reduce the branching density of polyethylenes compared with B-Cat. [18,[44][45][46] Chen et al synthesized a series of α-diimine Ni(II) complexes with various substituents on the backbone, and the α-diimine Ni(II) complexes with two methoxy substituents on the ortho position of the acenaphthyl backbone could produce polyethylene with three times higher molecular weight than that using B-Cat (Figure 1, IX). [25] Modification of the backbone part of an α-diimine ligand is another potential strategy for improving the catalyst's molecular-weight ability.…”
Section: Introductionmentioning
confidence: 99%